Case report: Analysis of phage therapy failure in a patient with a Pseudomonas aeruginosa prosthetic vascular graft infection - Blasco, Lucia; López-Hernández, Inmaculada; Rodríguez-Fernández, Miguel; Pérez-Florido, Javier; Casimiro-Soriguer, Carlos S.; Djebara, Sarah; Merabishvili, Maya; Pirnay, Jean-Paul; Rodríguez-Baño, Jesús; Tomás, María; López Cortés, Luis Eduardo (Frontiers in Medicine, 2023)
Clinical case of a patient with a Pseudomonas aeruginosa multidrug-resistant prosthetic vascular graft infection which was treated with a cocktail of phages (PT07, 14/01 and PNM) in combination with ceftazidime-avibactam (CZA). After the application of the phage treatment and in absence of antimicrobial therapy, a new P. aeruginosa bloodstream infection (BSI) with a septic residual limb metastasis occurred, now involving a wild-type strain being susceptible to ß-lactams and quinolones. Clinical strains were analyzed by microbiology and whole genome sequencing techniques. In relation with phage administration, the clinical isolates of P. aeruginosa before phage therapy (HE2011471) and post phage therapy (HE2105886) showed a clonal relationship but with important genomic changes which could be involved in the resistance to this therapy. Finally, phenotypic studies showed a decrease in Minimum Inhibitory Concentration (MIC) to ß-lactams and quinolones as well as an increase of the biofilm production and phage resistant mutants in the clinical isolate of P. aeruginosa post phage therapy.